Formulation and characterization of lamotrigine nasal insert targeted brain for enhanced epilepsy treatment - Rehab Abdelmonem; Hadel A. Abo El-Enin; Ghada Abdelkader; Mohamed Abdel-Hakeem (Taylor & Francis Group, 2023)
AbstractLamotrigine. (LMT) is a triazine drug has an antiepileptic effect but with low water solubility, dissolution rate and thus therapeutic effect. Spanlastics are nano-vesicular carriers' act as site-specific drug delivery system. Intranasal route could direct the drug from nose to brain and provide a faster and more specific therapeutic effect. Therefore, this study aimed to upload lamotrigine onto nano-vesicles using spanlastic nasal insert delivery for effective epilepsy treatment via overcoming lamotrigine's low solubility and improving its bioavailability. Lamtrigine-loaded nano-spanlastic vesicles were prepared by ethanol injection method. To study different formulation factor's effect on formulations characters; particle size (PS), Zeta potential (ZP), polydispersity index (PDI), entrapment efficiency percentage (EE%) and LMT released amount after 6 h (Q6h); 2^1 and 3^1 full factorial designs were employed. Optimized formula was loaded in lyophilized nasal inserts formulation which were characterized for LMT release and mucoadhesion. Pharmacokinetics studies in plasma and brain were performed on rats to investigate drug targeting efficiency. The optimal nano-spanlastic formulation (F4; containing equal Span 60 amount (100 mg) and edge activator; Tween 80) exhibited nano PS (174.2 nm), high EE% (92.75%), and Q6h > 80%. The prepared nasal inserts (S4) containing 100 mg HPMC has a higher mucoadhesive force (9319.5 dyne/cm2) and dissolution rate (> 80% within 10 min) for rapid in vivo bio-distribution. In vivo studies showed considerable improvement brain and plasma's rate and extent absorption after intranasal administration indicating a high brain targeting efficiency. The results achieved indicate that nano-spanlastic nasal-inserts offer a promising LMT brain targeting in order to maximize its antiepileptic effect.